2022
DOI: 10.3390/cells11060953
|View full text |Cite
|
Sign up to set email alerts
|

MRGPRX2-Mediated Degranulation of Human Skin Mast Cells Requires the Operation of Gαi, Gαq, Ca++ Channels, ERK1/2 and PI3K—Interconnection between Early and Late Signaling

Abstract: The recent discovery of MRGPRX2 explains mast cell (MC)-dependent symptoms independently of FcεRI-activation. Because of its novelty, signaling cascades triggered by MRGPRX2 are rudimentarily understood, especially in cutaneous MCs, by which MRGPRX2 is chiefly expressed. Here, MCs purified from human skin were used following preculture or ex vivo and stimulated by FcεRI-aggregation or MRGPRX2 agonists (compound 48/80, Substance P) in the presence/absence of inhibitors. Degranulation was assessed by β-hexosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 94 publications
4
26
0
Order By: Relevance
“…Both β-arrestin-1, and More Strongly β-arrestin-2, Counter MRGPRX2-Mediated Phosphorylation of ERK1/2 Figure 1 showed that β-arrestin-1 and β-arrestin-2 restrict MRGPRX2's secretory competence to a similar degree, whereas Figure 2 demonstrated that only β-arrestin-1 reduction supports MRGPRX2 expression, calling for an alternative modus operandi in the case of β-arrestin-2. In skin MCs, both ERK1/2 and AKT are crucial to granule discharge activated via MRGPRX2 or FcεRI, as demonstrated recently by us (26). We therefore postulated that β-arrestin-2 deficiency may promote phosphorylation events downstream of MRGPRX2.…”
Section: β-Arrestin-1 But Not β-Arrestin-2 Negatively Regulates Mrgpr...supporting
confidence: 53%
See 4 more Smart Citations
“…Both β-arrestin-1, and More Strongly β-arrestin-2, Counter MRGPRX2-Mediated Phosphorylation of ERK1/2 Figure 1 showed that β-arrestin-1 and β-arrestin-2 restrict MRGPRX2's secretory competence to a similar degree, whereas Figure 2 demonstrated that only β-arrestin-1 reduction supports MRGPRX2 expression, calling for an alternative modus operandi in the case of β-arrestin-2. In skin MCs, both ERK1/2 and AKT are crucial to granule discharge activated via MRGPRX2 or FcεRI, as demonstrated recently by us (26). We therefore postulated that β-arrestin-2 deficiency may promote phosphorylation events downstream of MRGPRX2.…”
Section: β-Arrestin-1 But Not β-Arrestin-2 Negatively Regulates Mrgpr...supporting
confidence: 53%
“…Foreskins from circumcisions were obtained with written informed consent of the patients or their legal guardians (26,42,46). The study was approved by the Ethics Committee of the Charité Universitätsmedizin Berlin (protocol code EA1/204/10, 9 March 2018) and experiments were conducted according to the Declaration of Helsinki Principles.…”
Section: Skin MC Purification and Culturementioning
confidence: 99%
See 3 more Smart Citations